What is Behind Labor Mobility Costs? Evidence from Indonesia - Cali, Massimiliano; Hidayat, Taufik; Hollweg, Claire H. (World Bank, Washington, DC, 2019)
The ability of workers to transition to a new job is crucial to determine the resilience of an economy to (positive or negative) shocks. This paper provides new evidence on the factors that affect labor mobility by using labor data on Indonesia, one of countries with the higher estimated labor mobility costs. To do so it investigates correlates of the probability of an individual finding a job after a negative labor market shock, as well as of the duration of job search. The results show that higher housing prices are associated with higher mobility costs, suggesting that housing benefits or policies that increase the supply of housing may help reduce mobility costs in Indonesia. More generally, public expenditure on infrastructure seems to reduce labor mobility costs, particularly in urban areas, consistently with a reduction in transaction costs – such as urban transport. The results also highlight that formal institutional mechanisms such as job advertisements do not appear to work effectively to help labor mobility in Indonesia, suggesting the need to re-think active labor market policies. On the other hand, minimum wage level – a key outcome of labor market policy - does not appear to affect labor mobility. Labor mobility costs seem higher in urban areas, which could indicate a lower opportunity cost of joblessness than in rural area, employment composition skewed towards sectors with higher mobility costs and/or large congestion costs that negatively affect labor mobility. On the other hand, the general female penalty in labor mobility is less accentuated in urban areas, which may be the result of sectoral composition and/or less discriminatory cultural norms than in rural areas.